MENINGKATKAN KUALITAS PUBLIKASI ILMIAH: WORKSHOP PENULISAN ARTIKEL KE JURNAL SCOPUS BAGI AKADEMISI DAN PRAKTISI - Ngatmin Abbas; Edy Muslimin; Mukhlis Fathurrohman; Alfian Eko Rochmawan (LPPM STAI Muhammadiyah Probolinggo, 2025)
Publishing scientific articles in reputable international journals such as Scopus and Web of Science (WoS) poses significant challenges for academics and practitioners in Indonesia. Many of them encounter obstacles in understanding writing standards, selecting appropriate journals, and navigating the peer review process. These limitations have resulted in low acceptance rates for articles in prestigious journals. Therefore, strategic efforts through Community Service Programs (Pengabdian kepada Masyarakat or PKM) are necessary to enhance the capacity of academics in writing and publishing scientific articles. The PKM activity aimed to improve the understanding and readiness of academics and practitioners for publication in reputable journals through a scientific article writing workshop. The methodology employed a participatory approach using interactive workshop formats, which included material presentations, writing practice sessions, and direct mentoring. A total of 25 participants engaged in the full-day event. Workshop results demonstrated that most participants experienced a significant increase in understanding regarding scientific article writing structure, strategies for journal selection, and article submission processes. Additionally, participants gained increased confidence in addressing review and revision procedures. The implications of this activity highlight the need for continuous support to ensure academics can effectively apply the knowledge acquired in scientific publications. The recommendation from this Community Service Program is to develop more comprehensive programs with longer durations and more intensive guidance. By doing so, academics and practitioners can continuously improve the quality of their scientific publications, ultimately enhancing academic competitiveness at the global level. Keywords: scientific publication; reputable journals; workshop; Community Service Program.